Circulating Tumor DNA Analyses as a Potential Marker of Recurrence and Effectiveness of Adjuvant Chemotherapy for Resected Non-Small-Cell Lung Cancer - Kuang, Peng-Peng; Li, Ning; Liu, Zui; Sun, Tian-Yu; Wang, Shu-Quan; Hu, Jia; Ou, Wei; Wang, Si-Yu (Frontiers in Oncology, 2021)
Background: Although adjuvant chemotherapy is established for patients with non-small-cell lung cancer (NSCLC), the long-term survival remains to be improved. Postsurgical circulating tumor DNA (ctDNA) analysis of resectable NSCLC may identify patients at high risk of recurrence after adjuvant chemotherapy and facilitate personalized therapy. Methods: This analysis included 38 patients who underwent curative-intent resection and received adjuvant chemotherapy for NSCLC. ctDNA analyses of tumor tissue, and pre- and post-operative plasma samples were performed with next-generation sequencing targeting 425 cancer-relevant genes. We define a ctDNA positive event as at least one shared mutation identified simultaneously in the plasma and tumor specimens. The primary endpoint was recurrence-free survival (RFS). Results: At least 1 somatic mutation was identified in the tumor tissue of all 38 patients. Tumor tissue-specific mutated ctDNA was detected in the preoperative plasma samples of 19 (50%) patients. ctDNA in preoperative plasma was in good accordance with that in tissue. ctDNA was detectable in the first post-operative pre-chemotherapy samples of 8 of 35 (22.9%) patients and was associated with inferior RFS (HR, 3.69; P=0.033). ctDNA was detected in the first post-chemotherapy samples of 8 of 36 (22.2%) patients and was also associated with inferior RFS (HR, 8.76; P < 0.001). Conclusions: Postoperative and post-chemotherapy ctDNA is a promising prognostic marker for resected NSCLC. ctDNA analyses may define a subgroup that remains at high risk of relapse despite standard adjuvant chemotherapy, and may help to inform intensified therapeutic strategies.